PENGARUH PERAN PENYULUH, MOTIVASI KERJA DAN SIKAP PETANI TERHADAP ADOPSI INOVASI PADI SAWAH DI ACEH BESAR - Syahputra, Andrian Wira; Hariadi, Sunarru Samsi; Harsoyo , Harsoyo (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2016)
The research is aimed to analyse: (1) the influence of the extension workers role on the innovation adoption of rice paddy field, (2) the influence of farmers work motivation on the innovation adoption of rice paddy field, (3) the influence of farmers attitudes on the innovation adoption of paddy field. The basic method used in this research was the descriptive analysis with the quantitative and qualitative approaches. The research location was chosen purposively namely Montasik Subdistrict in Aceh Besar district. The Sampling method to determine respondents was the Simple Random Sampling. There were 120 farmers involved in the study. The statistical method used was the multiple linear regression. The research results showed that the role of extension workers, the farmers motivations and attitudes influenced significantly to the adoption innovation of wet rice cultivation (α=10%), either partially and simultaneously.